Rachel Schmidt, Forms of Modernity: “Don Quixote” and modern theories of the novel. University of Toronto Press, Toronto, 2011; 403 pp. - Iglesias, Mariana (El Colegio de México, 2015)
Se reseña el libro:Forms of Modernity: “Don Quixote” and modern theoriesof the novel.